ASPECT VARIATION IN NARRATIVE: A DISCOURSE APPROACH - Rivas Carmona, María del Mar (ELIA: Estudios de Lingüística Inglesa Aplicada, 2017)
Abstract The aim of this paper is to show how the choice of verbal aspect may not just be a matter of location in time but also a sign of the addresser’s intentions to highlight different elements of the message. The role of the addressee is to establish temporal assumptions and draw the necessary inferences in order to interpret the text. In the case of literary texts, writers make use of aspect variation in order to foregroud particular events and to involve or detach the readers with respect to them. Thus, writers take advantage of these camera-angle possibilities and we may find instances where sentences containing the progressive or imperfective aspect convey events as if from within a character’s mind or as if the reader were close to the scene, scrutinizing all the details. We will illustrate this with some excerpts from novels by Virginia Woolf, Jean Rhys, Margaret Drabble and Doris Lessing, in which temporal inferencing plays a vital role when distinguishing subjective fragments of thought-representation from objective fragments of narration.